PENGEMBANGAN DESAIN PEMBELAJARAN PAI MELALUI IMPLEMENTASI KURIKULUM MERDEKA DI SDN 3 NASOL, CIKONENG KABUPATEN CIAMIS - Asep Samsul Umam; Muhammad Rofi Shohibuddin; Selamet (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of Islamic Religious Education (PAI) learning design has become an urgent need to realize learning that aligns with the demands of the Merdeka Curriculum. This study explores how the implementation of the Merdeka Curriculum at SDN 3 Nasol contributes to the innovation of PAI learning design oriented toward learner autonomy and the strengthening of the Pancasila Student Profile. A qualitative approach with a case study method was employed. Data were collected through classroom observations, in-depth interviews with PAI teachers and the school principal, and an analysis of lesson planning documents. Data analysis was conducted interactively through data reduction, presentation, and conclusion drawing. The findings indicate that the implementation of the Merdeka Curriculum has significantly transformed the PAI learning design in terms of planning, instructional strategy, and evaluation. Teachers have become more creative in designing project-based learning activities connected to the Pancasila Student Profile, emphasizing collaboration, reflection, and spiritual values. This transformation has enhanced students’ engagement, motivation, and religious understanding in daily life. Overall, the implementation of the Merdeka Curriculum serves as a strategic foundation for pedagogical transformation toward a more humanistic, contextual, and student-centered PAI learning process.